PERSEPSI KONSEP DIRI ORANG DENGAN HIV/AIDS (ODHA) DALAM KELOMPOK DUKUNGAN SEBAYA (KDS) DI KOTA DAN KABUPATEN KEDIRI - Rusmawati, Aprin (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Perception is a kind of mental process which is accepted with stimulant of individu through five perception. There is stigma and discrimination against people with HIV/AIDS that can cause disturbance for self – concept. Self – concept here covers body image, self – ideal, self – respect, self – role and self – identity. People think that HIV/AIDS is a disease that can kill contigious people easily. One of the main purpose of Equivalent Supported Group is to decrease or eliminate the stigma an discrimination in order that people with HIV/AIDS can empower and socialize with community. The purpose of this research was to know perception of self – concept people with HIV/AIDS in Equivalent Supported Group in municipality and regency of Kediri. The research is a kind of descriptive research that describe urgent events happened in the past. The unit of analysis in the research is all of the people with HIV/AIDS in Equivalent Supported Group in municipality and regency of Kediri who are willing to be respondents. The instrument is an interview and procedure of collecting data through in depth interview. From the research for the self – concept people with HIV/AIDS, it can be recognized that the changes of physical appeareance people with HIV/AIDS cause of HIV/AIDS are not influenced in contact with community and make them humble or low respect. Principally, most of the informen are ready to accept their status as people with HIV/AIDS because of the equivalent friend and family support. Some informen unbelieve that they are categorized HIV positive because some of informen have not experienced any symptoms related to HIV. The role of Equivalent Supported Group is a secure and comfortable institution or place for those with people with HIV/AIDS and those living with HIV/AIDS to get together and meet. In open and close meeting held by Equivalent Supported Group, people with HIV/AIDS and those living with HIV/AIDS can get new information about HIV/AIDS and other diseases connected with HIV.